Estruturas paratáticas de que-conetivo em frases não-argumentais - Matos, Gabriela; Rodrigues, Patrícia (Revista da Associação Portuguesa de Linguística, 2020)
In European and Brazilian Portuguese gramatical tradition, non-argumental clauses introduced by que ‘that’ have been classified as causal explicative clauses. However, differently from the other explicative conetives, que may head non-argumental clauses displaying other meanings, such as result/consequence or simultaneous temporal readings. We take these different readings as resulting from the context, and we assume that the main semantic import of que is acting as a sentence connector marker. Yet, despite the differences in the interpretation of queclauses, from a syntactic point of view, these clauses behave alike. We argue that they are parenthetical sentences, extending previous work on European Portuguese.